LeafJ: An ImageJ Plugin for Semi-automated Leaf Shape Measurement - Maloof, Julin N. (MyJove Corporation, 2013)
High throughput phenotyping (phenomics) is a powerful tool for linking genes to their functions (see review(1) and recent examples(2-4)). Leaves are the primary photosynthetic organ, and their size and shape vary developmentally and environmentally within a plant. For these reasons studies on leaf morphology require measurement of multiple parameters from numerous leaves, which is best done by semi-automated phenomics tools(5,6). Canopy shade is an important environmental cue that affects plant architecture and life history; the suite of responses is collectively called the shade avoidance syndrome (SAS)(7). Among SAS responses, shade induced leaf petiole elongation and changes in blade area are particularly useful as indices(8). To date, leaf shape programs (e.g. SHAPE(9), LAMINA(10), LeafAnalyzer(11), LEAFPROCESSOR(12)) can measure leaf outlines and categorize leaf shapes, but can not output petiole length. Lack of large-scale measurement systems of leaf petioles has inhibited phenomics approaches to SAS research. In this paper, we describe a newly developed ImageJ plugin, called LeafJ, which can rapidly measure petiole length and leaf blade parameters of the model plant Arabidopsis thaliana. For the occasional leaf that required manual correction of the petiole/leaf blade boundary we used a touch-screen tablet. Further, leaf cell shape and leaf cell numbers are important determinants of leaf size(13). Separate from LeafJ we also present a protocol for using a touch-screen tablet for measuring cell shape, area, and size. Our leaf trait measurement system is not limited to shade-avoidance research and will accelerate leaf phenotyping of many mutants and screening plants by leaf phenotyping.